Efficacy of a Condom Negotiation Intervention among High Risk Iranian Women in Tehran, Iran - Zahra Bayat JOZANI; SeyedAhmad SEYEDALINAGHI; Saeedeh MOAYEDI-NIA; Mohadese BEHTAJ; Mostafa SHOKOOHI; Minoo MOHRAZ; Farzaneh VAKILI; Hoorvash Fraji DANA (国际转化医学杂志（英文版）, 2018)
Background: Development of tailored interventions to promote condom use seems essential in countries with traditional gender role definitions. Learning condom influence strategies could be helpful when it is difficult for women to initiate sexual communication. These strategies have been targeted in a safer sex skills building intervention among high-risk women in Tehran, Iran. Methods: We conducted this study among 50 high-risk women who registered for counseling and HIV testing at Imam Khomeini Hospital in Tehran, Iran, 2012-2013. Participants were assigned to two groups: 1) routine 15 minute pre-test HIV counseling, or 2) routine counseling besides communication skills building monthly sessions for six months. Pre and post-tests were taken at baseline and six months. We designed an intervention based on Information-Motivation-Behavior theory. Condom influence strategies were used in the construct of the questionnaire and intervention materials. Results: After six months participants in the intervention group were able to implement influence strategies to promote partners' condom use (P = 0.01). Risk information and relationship conceptualizing were more endorsed post-intervention (P = 0.02, P =0.006). In addition, partner communication had significantly improved in the case group (P < 0.001). Conclusions: We found that condom influence strategies could be considered in improving current counseling sessions, as an effective intervention to minimize HIV and other Sexually Transmitted Infections (STIs) transmission among high-risk women. We recommend this skill-based intervention for condom negotiation to empower at-risk sexually active women.